2019
DOI: 10.1111/cas.13940
|View full text |Cite|
|
Sign up to set email alerts
|

Bazedoxifene exhibits growth suppressive activity by targeting interleukin‐6/glycoprotein 130/signal transducer and activator of transcription 3 signaling in hepatocellular carcinoma

Abstract: The interleukin (IL)‐6/glycoprotein (GP)130/signal transducer and activator of transcription (STAT)3 pathway is emerging as a target for the treatment of hepatocellular carcinoma. IL‐6 binds to IL‐6R, forming a binary complex, which further combines with GP130 to transduce extracellular signaling by activating STAT3. Therefore, blocking the interaction between IL‐6 and GP130 may inhibit the IL‐6/GP130/STAT3 signaling pathway and its biological effects. It has been reported that bazedoxifene acetate (BAZ), a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 47 publications
3
28
0
Order By: Relevance
“…Subsequently, it suppresses STAT3 phosphorylation and transcription induced by IL6. Various studies have shown Bazedoxifene could inhibit tumor growth by targeting the IL-6/GP130/STAT3 signaling pathway (Wu et al, 2016;Xiao et al, 2017;Chen et al, 2019;Ma et al, 2019). Based on our study, we found Bazedoxifene could attenuate the formation and severity of aneurysms, which may expand the application of Bazedoxifene to the prevention and treatment of abdominal aortic aneurysms in clinics.…”
Section: Discussionsupporting
confidence: 59%
“…Subsequently, it suppresses STAT3 phosphorylation and transcription induced by IL6. Various studies have shown Bazedoxifene could inhibit tumor growth by targeting the IL-6/GP130/STAT3 signaling pathway (Wu et al, 2016;Xiao et al, 2017;Chen et al, 2019;Ma et al, 2019). Based on our study, we found Bazedoxifene could attenuate the formation and severity of aneurysms, which may expand the application of Bazedoxifene to the prevention and treatment of abdominal aortic aneurysms in clinics.…”
Section: Discussionsupporting
confidence: 59%
“…The pathology that murine model mimics differs from HHD in humans. Studies have proved that Bazedoxifene inhibits IL‐6/gp130 signalling pathway in several types of cancer, but whether the observed benefit of Bazedoxifene intake is dependent of IL‐6 signalling in pressure overload mice has not been established. Notably, the 3‐hour to 8‐week results suggested the sustained STAT3 activation and dynamic alteration of LC3 conversion might participate throughout the whole follow‐up, which indicated the potential requirement of durative Bazedoxifene administration, while the mechanisms underlying the adverse effect of Bazedoxifene on LC3‐II/LC3‐I in acute window and the long term need further study to clarify.…”
Section: Discussionmentioning
confidence: 99%
“…Using multiple ligand simultaneous docking (MLSD) and drug repositioning, Li et al showed bazedoxifene and raloxifene, which are approved agents for osteoporosis in post-menopausal women with high risk of breast cancer, could inhibit IL-6/glycoprotein 130 interaction resulting in inhibited IL-6 signaling [ 123 ]. These two drugs are found to inhibit IL-6 signaling in tumor and cardiovascular disease including aortic aneurysm [ [124] , [125] , [126] , [127] ], which may also effect in other inflammatory settings. In a randomized, double-blind trial conducted by Ridker PM et al, antiinflammatory treatment by anti-IL-1β antibody canakinumab decreased the rate of recurrent cardiovascular events than placebo [ 128 ].…”
Section: Promising Strategies For Hypercoagulability In Covid-19mentioning
confidence: 99%